CRISPR/Cpf1–FOKI-induced gene editing in Gluconobacter oxydans - Xuyang Wang; Dong Li; Zhijie Qin; Jian Chen; Jingwen Zhou (Synthetic and Systems Biotechnology, 2024)
Gluconobacter oxydans is an important Gram-negative industrial microorganism that produces vitamin C and other products due to its efficient membrane-bound dehydrogenase system. Its incomplete oxidation system has many crucial industrial applications. However, it also leads to slow growth and low biomass, requiring further metabolic modification for balancing the cell growth and incomplete oxidation process. As a non-model strain, G. oxydans lacks efficient genome editing tools and cannot perform rapid multi-gene editing and complex metabolic network regulation. In the last 15 years, our laboratory attempted to deploy multiple CRISPR/Cas systems in different G. oxydans strains and found none of them as functional. In this study, Cpf1-based or dCpf1-based CRISPRi was constructed to explore the targeted binding ability of Cpf1, while Cpf1–FokI was deployed to study its nuclease activity. A study on Cpf1 found that the CRISPR/Cpf1 system could locate the target genes in G. oxydans but lacked the nuclease cleavage activity. Therefore, the CRISPR/Cpf1–FokI system based on FokI nuclease was constructed. Single-gene knockout with efficiency up to 100% and double-gene iterative editing were achieved in G. oxydans. Using this system, AcrVA6, the anti-CRISPR protein of G. oxydans was discovered for the first time, and efficient genome editing was realized.